(untitled) (Innovative professional education, 2022)
The publication raised the problem of conducting educational process in a scientific institution, highlighted its peculiarities. It has been characterized the training of higher education seekers at the master’s level (specialty 011 Educational, pedagogical sciences) andPhD (specialty 015 Professional education) at the Institute of Vocational Education of the National Academy of Educational Sciences of Ukraine. The problems and prospects of the development of educational programs are defined.